Enabling Environmental Justice Through Education and Conservation: The Status of Existing University Curricula Relating to Environmental Justice (Discipline – Environment) - Khanal, Sanjay Nath; Krishna Murthy, V. (Kathmandu University Journal of Science, Engineering and Technology, 2007)
The intent of the exercise was to have a comprehensive status paper on Environmental Justice (EJ) education available on one hand and desirable on the other to be prescribed in graduate and undergraduate levels of university education in Nepal. The present evaluation reports results of a review of existing syllabi of environmental science and environmental management taught at the three major universities namely Tribhuwan University (TU), Pokhara University (PU) and Kathmandu University (KU) at Undergraduate (UG) and Postgraduate (PG) levels. A simple evaluation scheme was designed to assess the representation of topics and subtopics under the selected categories of Environmental Justice. This central information of the report is supplemented by introductory account of EJ in Nepal as an academic discipline and review account of courses provided by other universities and other considerations in design and development of EJ curriculum. Notable among the conclusions are firstly to conceive and frame the syllabi affixing EJ as an independent subject of 3 credits each or in total about 50 hours of teaching in UG and PG levels; while the UG course should be more oriented towards theoretical inputs related to scope, philosophy, definitions etc., the PG course should focus on national and international perspectives and issues along with policies and plans. A professional approach in framing PG level syllabus is suggested with a provision to take up dissertation work related to EJ. In Nepal, it is time to sustain the participatory-based judicial dispensation with an intention of effective and useful implementation of policies by stakeholders. There is an essentiality of introducing the issues related to international environmental which are not only contextual but also futuristic. The report concludes by reiterating to consider the opinion and expertise to judicial officials at the time of framing the syllabi for teaching at graduate and undergraduate levels facilitating inclusion of essential components in an adequate and appropriate measure.